2020
DOI: 10.1111/ejh.13428
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of transfusion‐dependent congenital dyserythropoietic anemia Type I patients with pegylated interferon alpha‐2a

Abstract: ObjectivePegylated IFN‐α2a has been reported in two case reports as being efficacious in treating CDA‐I patients. This study aims to assess its efficacy on a series of CDA‐I patients.MethodsStudy sample consisted of seven CDA type 1 transfusion‐dependent patients. They received pegylated interferon alpha‐2a at an initial dose of 90‐180 µg once a week, tapered according to clinical response and side effects. Good response was defined as Hb ≥ 10 g/dL for ≥3 months, partial response was defined as 7 ≤ Hb<10 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Most transplants for CDA are performed in childhood (median age is 5.1 years) [68], although adult CDA patients have also successfully undergone bone marrow transplantation [80]. Except for Interferon alpha-2a, which was serendipitously found to reduce/halt hemolysis in CDA I by a yet unknown mechanism [37–41,42 ▪ ], there are no specific therapies for the CDAs, which reflects our poor understanding of the pathogenic mechanisms underlying these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most transplants for CDA are performed in childhood (median age is 5.1 years) [68], although adult CDA patients have also successfully undergone bone marrow transplantation [80]. Except for Interferon alpha-2a, which was serendipitously found to reduce/halt hemolysis in CDA I by a yet unknown mechanism [37–41,42 ▪ ], there are no specific therapies for the CDAs, which reflects our poor understanding of the pathogenic mechanisms underlying these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown improvement in the CDA I anemia with interferon treatment [37–41]. A recent cohort of CDA I patients showed that six out of seven patients achieved transfusion independence with pegylated interferon alpha-2a [42 ▪ ]. Notably, patients treated with pegylated interferon alpha-2a appear to have reduced hemolysis but continue to have high ferritin levels.…”
Section: Congenital Dyserythropoietic Anemia Type Imentioning
confidence: 99%
“…Ultra-structural erythroid features include “spongy” heterochromatin (“Swiss cheese type”), enlargement of the nuclear pores and invagination of the nuclear membrane. For some patients, administration of interferon-α (INF-α) improves anemia and normalizes erythroid morphology ( Lavabre-Bertrand et al, 2004 ; Abu-Quider et al, 2020 ), although this treatment has significant toxicities.…”
Section: Introductionmentioning
confidence: 99%